Drug-induced liver injury due to tofacitinib: a case report - Masoud Mardani; Jafar Mohammadshahi; Sara abolghasemi; Roghayeh Teimourpour (Journal of Medical Case Reports, 2023)
Abstract Background Drug-induced liver injury is an acute or chronic liver damage in response to drugs, herbals, and any chemical compound. Case presentation In the present work, liver failure following the use of tofacitinib was reported. The patient was an 18-year-old iranian woman without any history of underlying disease. She complained of alopecia areata, and tofacitinib was administered for disease management. Following adherence to tofacitinib medication, partial recovery was obtained. At the time of hospitalization, the patient had a stable condition and only anorexia, jaundice, and elevation of liver enzymes were reported. During hospitalization, liver injury progressed and liver transplantation was suggested. After drug-induced liver injury diagnosis, the use of the drug was discontinued and the patient underwent supportive treatment. The patient recovered without any severe sequelae. Conclusions Tofacitinib is a Janus kinase inhibitor that is useful in the treatment of disorders such as rheumatoid arthritis, psoriatic arthritis, and ulcerative colitis. Until now, the severe side effect of this drug has not been reported and in most cases it is used as a last resort, but here we report a rare side effect of this drug.